Under the weather - Tan, Hwee Ann (Nanyang Technological University, 2020)
Under the Weather is a short 3D animation film where a girl experiments with making sweets in her factory. She then feeds her rabbit and constantly fails, but eventually succeeds and launches the rabbit via a cannonout of her flying house into the sky. It is only after the rabbit poofs up into a cloud that we realise what her goal was all along. This report will elaborate on the process and development of this film.